Possibilities of the Application of Child Behaviour Observation as a Tool of Social Pedagogue Work - Indrašienė, Valdonė; Prakapas, Romas (Pedagogika, 2016)
The article reveals the topicality of child behaviour observation in the context of social education. Also, the focus is directed towards the ideas by Prof. Bronislovas Bitinas concerning the possibilities of the development of educational science and practice by relying on diagnostic results of child behaviour and activities. The actual problem is related to the application of observation as a working instrument while implementing social pedagogical activities of child behaviour correction. The aim of the article is to describe the possibilities of the application of child behavior observation as a tool of social pedagogue correctional activities for children from risk groups. The research was conducted by applying retrospective analysis, research data analysis and synthesis. The article defines the prerequisites of the development of the behaviour observation instrument devoted to the solution of delinquency prevention problems. The attention is paid to the argument by Prof. B. Bitinas that sporadic educational activities directed to individual work with children from risk groups are not effective. On the contrary, systematic activities including deviant child behaviour observation are necessary. Behaviour observation is analyzed not only as an instrument but also as a purposeful directed and organized cognitive process which creates the conditions to improve social pedagogical activities with children and the collection of the necessary information. Generally speaking about the behaviour observation instrument suggested by Prof. B. Bitinas and active participation in the development of the instrument and its application, it should be stressed that it is the first focused attempt to develop a scientifically based working instrument for social pedagogues. The appropriate and consistent application of the behaviour observation instrument in social education provides prerequisites for sensitively diagnosing the behavior and choosing well-timed, purposeful, directive and pedagogically sound behaviour correction strategies. Meaningful application of the behaviour observation instrument in social pedagogue work provides the background for more effective psycho-pedagogical work with children from risk groups.